Challenges of cancer survivorship care in Chile: a longitudinal study comparing the quality of care and quality of life for cancer survivors in a primary care network and a cancer centre in Chile - Jon Emery; Klaus Püschel; Beti Thompson; Victor Arancibia; Andrea Rioseco; Sarah Paz; María Gabriela Soto; Javiera Martinez; Marcela Faundez; Francisco Acevedo; Felipe Di Biase; Augusto León; et al. (BMJ Open)
Objective The rapid growth in the cancer survivor population in Chile and Latin America raises new challenges in addressing their care needs. This study assesses the health status and compares the quality of care and quality of life in cancer survivors at a primary care network and a private cancer centre in Santiago, Chile.Design Retrospective cohort study.Setting Three primary care clinics and one cancer centre in Chile.Participants All breast and colorectal cancer patients identified from a primary care retrospective cohort of 61 174 were followed from 2018 to 2023 and compared with an equivalent sample of patients from a university cancer centre identified during the same period.Outcome measures Quality of care was assessed based on American Cancer Society standards, while quality of life was measured using the EuroQol 5 Dimensions-5 Levels survey instrument.Results A total of 420 cancer survivors participated in the study; 208 from primary care and 212 from the cancer centre. All participants received substandard care. Patients in primary care had lower educational levels and higher rates of comorbidity. They reported a lower quality of life score (72.22 vs 78.43, p<0.001), a higher prevalence of chronic pain (37.02% vs 25.6%, p=0.016) and more severe mental health symptoms (19.89% vs 10.05%, p=0.03). Differences in educational level and cancer stage at diagnosis explained the observed disparities in chronic pain and mental health disorders between the two populations. Primary care patients received more psychosocial care (OR=2.29; 95% CI: 1.55 to 3.39), cardiovascular assessment (OR=2.66; 95% CI:2.17 to 3.26) and psychosocial evaluations (OR: 9.07; 95% CI:4.75 to 17.32).Conclusion Cancer survivors face a significant disease burden and receive substandard care in Chile. As the primary source of care for this population, primary care is challenged to better integrate with speciality care to develop an effective shared care model for cancer survivors.